2018
DOI: 10.3892/ol.2018.8509
|View full text |Cite
|
Sign up to set email alerts
|

Combined overexpression of cadherin 6, cadherin 11 and cluster of differentiation 44 is associated with lymph node metastasis and poor prognosis in oral squamous cell carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is a highly invasive lesion that frequently metastasizes to the cervical lymph nodes and is associated with a poor prognosis. Several adhesion factors, including cadherin 6 (CDH6), cadherin 11 (CDH11) and cluster of differentiation 44 (CD44), have been reported to be involved in the invasion and metastasis of multiple types of cancer. Therefore, the aim of the present study was to determine the expression of CDH6, CDH11 and CD44 in tumor tissues from patients with OSCC, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…CXCL12 derived from tumor fibroblasts is known to promote tumor-cell invasion in breast cancer 55,56. CDH11, an adhesion molecule, is involved in pancreatic cell migration,57 and its overexpression, combined with Cdh6 and CD44, is associated with lymph-node metastases and poor prognosis in oral carcinoma 58. Finally, MYCL1 has not been reported to play a role in metastasis, but is recurrently amplified in Merkel-cell carcinoma59 and its genetic deletion in lung cancer models leads to strong tumor suppression 60…”
Section: Discussionmentioning
confidence: 99%
“…CXCL12 derived from tumor fibroblasts is known to promote tumor-cell invasion in breast cancer 55,56. CDH11, an adhesion molecule, is involved in pancreatic cell migration,57 and its overexpression, combined with Cdh6 and CD44, is associated with lymph-node metastases and poor prognosis in oral carcinoma 58. Finally, MYCL1 has not been reported to play a role in metastasis, but is recurrently amplified in Merkel-cell carcinoma59 and its genetic deletion in lung cancer models leads to strong tumor suppression 60…”
Section: Discussionmentioning
confidence: 99%
“…However, those genes were not detected at 8 weeks after PHMG exposure. Meanwhile, at 8 weeks after PHMG exposure, lung cancer-related genes such as TOP2A and MKI67 and tumor metastasis-related genes such as CDH11 and CD44 were significantly upregulated 12 15 .
Figure 4 Analysis of PHMG-regulated gene expression in rat lung tissue.
…”
Section: Resultsmentioning
confidence: 98%
“…There are additional studies suggesting that CDH6 is an important EMT marker in PTC as it can promote PTC metastasis by participating in the regulation of autophagy, thus leading to a poor prognosis [39]. Ma et al suggest that CDH6 is signi cantly up-regulated in patients with lymph node metastasis in oral squamous cell carcinoma (OSCC) and that patients have a poor prognosis [40]. It was further suggested that, when combined with other adhesion factor-related genes, CDH6 can be used as an important biomarker for OSCC lymph node metastasis and prognosis [40].…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al suggest that CDH6 is signi cantly up-regulated in patients with lymph node metastasis in oral squamous cell carcinoma (OSCC) and that patients have a poor prognosis [40]. It was further suggested that, when combined with other adhesion factor-related genes, CDH6 can be used as an important biomarker for OSCC lymph node metastasis and prognosis [40]. An in vivo study by Karthikeyan et al con rmed that CDH6 was inhibited by mutant p53 in high-grade serous ovarian cancer, which suggests that CDH6 may be a biomarker for this condition [41].…”
Section: Discussionmentioning
confidence: 99%